Crossing the line: Seroprevalence and risk factors for transboundary animal diseases along the Tanzania-Zambia border - Lysholm, S.; Lindahl, Johanna F.; Munyeme, M.; Misinzo, G.; Mathew, C.; Alvåsen, K.; Dautu, G.; Linde, S.; Mitternacht, L.; Olovsson, E.; Wilén, E.; Berg, M.; et al. (Frontiers Media, 2022)
Transboundary pathogens pose a threat to livelihood security in countries such as Zambia and Tanzania. This study aimed to investigate the seroprevalence of peste des petits ruminants virus (PPRV), foot and mouth disease virus (FMDV), sheep and goat pox virus (SGPV), Rift Valley fever virus (RVFV) and Brucella spp. in sheep and goats along the Tanzania-Zambia border. Another aim was to assess the association between certain predictor variables and seroprevalence, focusing on trade and proximity to an international border, to a town and to the Tanzania-Zambia highway. During September-October 2018, 486 serum samples from small ruminants in Zambia and 491 in Tanzania were collected and analyzed using enzyme-linked immunosorbent assays (ELISA). A questionnaire focused on management strategies was administered to each household. The animal-level seroprevalence in Zambia was 0.21% [95% confidence interval (CI) (0.01–1.14) for PPRV, 1.03% (95% CI 0.33–2.39) for FMDV, 0% (95% CI 0–0.76) for SGPV, 2.26% (95% CI 1.14–4.01) for RVFV and 1.65% (95% CI 0.71–3.22) for Brucella spp.]. In Tanzania, animal-level seroprevalence was 2.85% (95% CI 1.57–4.74) for PPRV, 16.9% (95% CI 13.7–20.5) for FMDV, 0.20% (95% CI 0.01–1.13) for SGPV, 3.26% (95% CI 1.87–5.24) for RVFV and 20.0% (95% CI 14.5–26.5) for Brucella spp. For PPRV (OR 6.83, 95% CI 1.37–34.0, p = 0.019) and FMDV (OR 5.68, 95% CI 1.58–20.3, p = 0.008), herds situated more than 30 km from an international border were more likely to be seropositive, while being located 10–30 km (OR 4.43, 95% CI 1.22–16.1 p = 0.024) from a border was identified as a risk factor for Brucella spp. For FMDV (OR 79.2, 95% CI 4.52–1388.9, p = 0.003), being situated within 30 km from a town was associated with seropositivity. Furthermore, contact with wild ruminants (OR 18.2, 95% CI 1.36–244), and the presence of sheep in the household (OR 5.20, 95% CI 1.00–26.9, p = 0.049), was associated with seropositivity for PPRV, and FMDV. No significant associations between trade or distance to the Tan-Zam highway and seroprevalence were found. We recommend that the impact of trade and proximity to borders, towns and roads should be further evaluated in larger studies, ideally incorporating aspects such as temporal trade fluctuations.